Financial Literacy; Strategies and Concepts in Understanding the Financial Planning With Self-EfficacyTheory and Goal SettingTheory of Motivation Approach - Muizzuddin, Muizzuddin; Taufik, Taufik; Ghasarma, Reza; Putri, Leonita; Adam, Mohamad (International Journal of Economics and Financial Issues, 2017)
This article discusses the strategies and concepts in understanding the financial literacy with the approach of self-efficacy theory and goal setting theory of motivation. The discussion begins with the concept of behavioral finance that discusses links between financial concepts to the behavior, and then proceed with the concept and measurement of financial literacy of individuals altogether with some approaches and factors that may affect it. Self-efficacy theory and goal setting theory of motivation is proposed to be a predictive factor of the level of financial literacy with relevant constructs, there are two propositions proposed to predict the level of financial literacy: (1) self-efficacy theory, in this case the motivational construct (manage finances, use credit cards less, and control debt);and (2) goal setting theory of motivation, in this case the goal commitment and goal specificity construct (financial planning). Keyword: financial literacy, self-efficacy, goal setting. JEL Classifications: G02, G3, L2